(untitled) (Journal of Pathology of Nepal, 2021)
Background: Neonatal sepsis continues to be a major public health problem in developing countries. Due to the nonspecific clinical manifestations of neonatal sepsis, the longer turnaround time for culture reports, an early diagnostic tool is essential for the initiation of appropriate and timely treatment. Materials and Methods: This is a cross-sectional study of 470 clinically suspected cases of neonatal sepsis admitted in the pediatrics department of B.P. Koirala Institute of Health Sciences, Dharan, Nepal. Following hematological parameters: abnormal total leucocyte count, abnormal total polymorphonuclear count, elevated immature Neutrophils count, elevated immature to total neutrophil ratio, immature to mature neutrophils ratio ≥ 0.3, platelet count ≤ 150,000/mm3, and pronounced degenerative changes in Neutrophils were assessed and a score of 1 was assigned to each as per the hematological scoring system of Rodwell. A score ≥ 3 was considered positive and a score < 3 was considered negative for the diagnosis of sepsis. Blood culture was taken as a gold standard for diagnosis of neonatal sepsis Results: Hematological scoring system had fairly high sensitivity, specificity, NPV, and PPV; i.e. 85.96%, 84.26%, 84.52%, and 85.71% respectively. The diagnostic accuracy of HSS was high (85.1%) in comparison to the maximum diagnostic accuracy of individual hematological parameters, i.e. 74.46% for the total neutrophil count. Conclusions: Hematological scoring system can be used as a convenient and early diagnostic tool against neonatal sepsis in developing countries with a high burden of neonatal sepsis because of its high sensitivity and easy availability.